GAMBARAN HEALTH BELIEF MODEL PADA PASIEN STROKE DI PENGOBATAN TRADISIONAL USTAD X: Health Belief Model; Stroke; Pengobatan Tradisional - asfy, Ibnu; Rida Yanna Primanita (CV. Causalita Dynamic Solutions, 2024)
Stroke is the third leading cause of death after heart disease and cancer. Although stroke cases are increasing and accompanied by rapid advances in medical treatment, people prefer the use of traditional medicine because the costs incurred are cheaper than medical treatment and they believe that using alternative (traditional) medicine is safer and faster to recover compared to chemical drugs measured through the health belief model theory. The purpose of this study was to look at the description of the health belief model in stroke patients at ustad X's traditional treatment. This study uses descriptive quantitative methods. The population in this study were patients with stroke who sought treatment at Ustadz X Traditional Medicine with a sample size of 32 people. Sampling in this study using non probability sampling technique with accidental sampling type. The results showed that stroke patients at Ustadz X's traditional treatment had a health belief model categorized at a high level both in the perception of vulnerability of 30 respondents (93.8%), perceived severity of 24 respondents (75%), perceived benefits of 31 respondents (96.9%), perceived barriers of 32 respondents (100%), and cues to take action 25 respondents (78.1%).